2020
DOI: 10.1016/j.solener.2020.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental validation of solar radiation distribution on the absorber of a line-axis asymmetric compound parabolic concentrator

Abstract: This paper reports the development and application of a new practical photovoltaic (PV) cells based device to measure the solar radiation flux produced by non-imaging Compound Parabolic Concentrators (CPCs) on cylindrical absorbers. The flexible experimental device comprises 12 discrete miniature PV panels that measure solar radiation on the surface of a cylindrical absorber. The device has been used to evaluate the performance of an asymmetric CPC system and results validated with a computer-based Ray Tracing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The system integrated PV technology and introduced a non-imaging Compound Parabolic Concentrator (CPC) for improved solar thermal collection performance of the cylindrical thermal diode ICSSWH. The reported optical performance results[45] of the AFRICaS ICSSWH subsystem indicated potential success for water heating at equatorial latitudes. Fig.1depicts the overall definition of the modular AFRICaS PHST proposition to support combined basic electricity and thermal energy demands at an entry-level scale for off-grid households in developing countries.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The system integrated PV technology and introduced a non-imaging Compound Parabolic Concentrator (CPC) for improved solar thermal collection performance of the cylindrical thermal diode ICSSWH. The reported optical performance results[45] of the AFRICaS ICSSWH subsystem indicated potential success for water heating at equatorial latitudes. Fig.1depicts the overall definition of the modular AFRICaS PHST proposition to support combined basic electricity and thermal energy demands at an entry-level scale for off-grid households in developing countries.…”
mentioning
confidence: 88%
“…Using a ground reflectance of 0.2 (sand/dry grass) and the diffuse fraction empirical formulation in Eq. ( 1), the estimated monthly average daily solar irradiation incident on the aperture tilt angle of 15° of the south facing AFRICaS PHST prototype [45] is 𝐻 𝑇 (𝛽 = 15°) = 4.61 kWh m 2 ⁄ day ⁄…”
Section: Pv Subsystem Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that PTC is theoretically possible for usage involving thermal energy up to 150°C. In their study on PTC design for solar energy harvesting, Researchers [18] used both experimental and simulation methods. We evaluated and assessed the newly built PT solar collector's performance.…”
Section: Introductionmentioning
confidence: 99%